HUBUNGAN TINGKAT KONSUMSI ENERGI DAN PROTEIN DENGAN STATUS GIZI ANAK BALITA DI WILAYAH KERJA PUSKESMAS TALISE KECAMATAN MANTIKULORE KOTA PALU - Windy Wiena Putri; Jamaluddin Sakung; Rochfika Suleiman (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2017)
Nutritional problems still being main problems in countries such as Indonesia developing. Nutrition status is the one of indicators. Nutrition status of someone affected by variety of factors. The purpose to know what a correlation between the consumption level of energy and protein with nutrition status of kids under five years old in the work Public Health Centre Talise Mantikulore Palu. The method used is analytic survey that use crross sectional, with 73 respondent as sample, the analytic used in this research are univariat and bivariat analyzes by chi-square test.The results of statistical chi square test showed that is meaningful relation between the adequacy of energy and nutrition status of under five children by the P Value 0,001and there is no meaningful relation between the adequacy of protein and nutrition status ofunder five children by the P Value=0,222.Expected to health workers in Public Health CentreTalise to increase the health services for public especially nutrition program. To hold information about the importance of the consumption level of energy or protein. That decline of under five childrenexperienced lack of energy and protein so that it can be create degrees public health maximum. Keyword : Consumption Level of Energy, Protein, Nutritional Status